Keteladanan dan Home Visit Berbasis Safari Tadarus Bentuk Kolaborasi Guru dengan Orang Tua dalam Mewujudkan Sekolah Ramah Anak di PAUD Matsaratul Huda Pamekasan - Ulfa Ainun Nikmah (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
This research is based on the urgency for teachers and parents to become role models for young children besides in guiding and educating children at school and home. A part from that, there is a tadarus safari-based home visit activity by visiting each child’s house in turn to train children from an early age to live socially, teachers can know and understand the condition of each child, and parents can consult intensively with teachers to find out the strengths and weakness of their children at school. This research aims to determine the form of teacher example towards early childhood and tadarus safari-based home visits in child-friendly schools. The method used is descriptive qualitative with a case study approach as well as interview and observation techniques. The results obtained in this research indicate that exemplary attitudes from teachers and parents have an effective influence in shaping children’s positive behavior. Then tha tadarus safari-based home visit activity is conducted by visiting each child’s home which included reciting Al-Qur’an and reviewing its meaning, communicating and evaluating.